Resin composition, polyester film, method for producing polyester film, and metal-laminated film

JP2025033564APending Publication Date: 2025-03-13MITSUBISHI CHEM CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023139349
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、従来並みの電気特性を維持しつつ、それでいて耐熱性が良好であり、薄膜化対応が可能であり、厚みムラの小さい、コンデンサー用として有用なポリエステルフィルムおよびその製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025033564000001
    Figure 2025033564000001
  • Figure 2025033564000002
    Figure 2025033564000002
Patent Text Reader

Abstract

To provide a polyester film which has good heat resistance while maintaining electric characteristics equivalent to conventional one, is adaptive to thinning, has good thickness unevenness, and is useful as a capacitor, and a method for producing the polyester film.SOLUTION: A resin composition is provided, including polyester resin (X), polypropylene resin (Y) and a compatibilizing agent (Z), and satisfying the following (1) and (2). (1) An MFR (melt flow rate) of the polypropylene resin (Y) is 7.0 g / 10 min or less. (2) The compatibilizing agent (Z) is resin or an ionomer having acid anhydride structure [-C(=O)-O-C(=O)-].
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a polyester film, a method for producing a polyester film, and a metal laminated film. [Background technology]

[0002] Polyethylene terephthalate (PET) film, a representative polyester film, especially biaxially oriented PET film, is widely used in a variety of fields, including industrial materials, optical materials, electronic component materials, and battery packaging materials, due to its excellent transparency, mechanical strength, heat resistance, and flexibility.

[0003] In addition, due to their excellent electrical properties, such as low dielectric loss, and high moisture resistance, resin films such as biaxially oriented polypropylene films are used as dielectric films for capacitors, such as filter capacitors and smoothing capacitors for high-voltage capacitors, various switching power supplies, converters, inverters, and the like. In recent years, there has been a demand for further miniaturization and higher capacity of capacitors. For example, when using a resin film in a capacitor for an inverter power supply device that controls the drive motor of an electric vehicle, a hybrid vehicle, or the like, small size, light weight, and high capacity are required (see Patent Document 1). As the capacity of a capacitor increases, there is a trend for it to be required to have high voltage resistance characteristics (capacitance stability) over a long period of time, for example, in a temperature range exceeding 120°C. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2014-231584 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, for example, in the case of a general-purpose biaxially oriented polypropylene film, while the electrical properties are good, when the temperature range of use is 120°C or higher, the heat resistance of the film itself reaches a limit level, making it difficult to deal with. Furthermore, when forming a cast film by T-die molding, particularly when attempting to form a film at high speed, periodic thickness fluctuations called "draw resonance" may occur in the running direction (MD) of the film. When this draw resonance phenomenon occurs, thickness unevenness occurs in the film, and breakage occurs frequently during film formation. In particular, in the present invention, a resin that is incompatible with polyester resin is used in combination with the polyester resin, and the environment is prone to thickness fluctuations, but even in the extremely thin film thickness range of 12 μm or less, slight thickness unevenness tends to drastically reduce film formability, and there was a situation in which thickness management at a higher level was required.

[0006] Therefore, the present invention has been made in consideration of the above problems, and proposes a polyester film that maintains electrical properties comparable to those of conventional films, yet has good heat resistance, can be made thinner, and has little thickness variation, making it useful for capacitors, and a method for producing the same. [Means for solving the problem]

[0007] As a result of extensive investigations, the present inventors have found that the above problems can be solved by employing a polyester film using a resin composition having a specific composition and a method for producing the same, and have completed the present invention as described below. That is, the present invention provides the following [1] to

[13] . [1] A resin composition comprising a polyester resin (X), a polypropylene resin (Y) and a compatibilizer (Z), which satisfies the following (1) and (2): (1) The polypropylene resin (Y) has an MFR (melt flow rate) of 7.0 g / 10 min or less. (2) The compatibilizer (Z) is a resin or ionomer having an acid anhydride structure [-C(=O)-O-C(=O)-]. [2] The resin composition according to the above [1], which contains 0.01 to 40 parts by mass of a compatibilizer (Z) per 100 parts by mass of the polyester resin (X). [3] The resin composition according to the above [1] or [2], which contains 1 to 30 parts by mass of polypropylene resin (Y) per 100 parts by mass of polyester resin (X). [4] The resin composition according to any one of the above [1] to [3], wherein the polyester resin (X) has an intrinsic viscosity of 0.80 dL / g or less. [5] The resin composition according to any one of the above [1] to [4], wherein the polyester resin (X) is at least one selected from polyethylene terephthalate and polyethylene-2,6-naphthalate. [6] The resin composition according to any one of the above [1] to [5], wherein the polycondensation catalyst for the polyester resin (X) is a Ti-based catalyst. [7] A polyester film comprising the resin composition according to any one of [1] to [6] above. [8] The polyester film according to the above [7], having a thickness of 0.5 to 12.0 μm. [9] A polyester film having a thickness of 0.5 to 12.0 μm, comprising a polyester resin (X), a polypropylene resin (Y) and a compatibilizer (Z), wherein the compatibilizer (Z) is a resin having an acid anhydride structure [-C(=O)-OC(=O)-] or an ionomer.

[10] The polyester film according to any one of the above [7] to [9], which has a dielectric breakdown strength of 250 kV / μm or more.

[11] The method for producing a polyester film according to any one of the above [7] to

[10] , wherein the amorphous film has a thickness variation of 50 μm or less in the running direction.

[12] The method for producing a polyester film according to the above

[11] , wherein the draft ratio (lip gap / thickness of unstretched sheet) is 40 or less.

[13] A metal laminated film comprising the polyester film according to any one of the above [7] to

[10] and a metal layer provided on at least one surface of the polyester film. Effect of the Invention

[0008] According to the present invention, it is possible to provide a polyester film that maintains electrical properties comparable to those of conventional films, yet has good heat resistance, can be made thinner, and has little thickness variation, and is useful for capacitors, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] An example of an embodiment of the present invention will be described below, however, the present invention is not limited to the embodiment described below. [Resin composition] The resin composition of the present invention (hereinafter sometimes referred to as "the resin composition") contains a polyester resin (X), a polypropylene resin (Y) and a compatibilizer (Z). Each of the constituent components will be described in detail below.

[0010] <Polyester resin (X)> The polyester resin (X) which is the main component resin of the present resin composition may be a homopolyester or a copolymer polyester. The main component resin means the resin having the largest mass ratio in the present resin composition, and may account for 50 mass% or more, 75 mass% or more, 90 mass% or more, or 100 mass% of the resins constituting the present resin composition.

[0011] The homopolyester is preferably one obtained by polycondensation of an aromatic dicarboxylic acid and an aliphatic glycol, such as terephthalic acid or 2,6-naphthalenedicarboxylic acid, or ethylene glycol, diethylene glycol, 1,4-butanediol, or 1,4-cyclohexanedimethanol. Representative examples of homopolyesters include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene-2,6-naphthalate (PEN). In the present invention, polyethylene terephthalate (PET) and polyethylene-2,6-naphthalate (PEN) are particularly preferred, and these can also be used in combination.

[0012] On the other hand, when the polyester is a copolymer polyester, it is preferable that the polyester is a copolymer containing 30 mol % or less of a third component. Examples of the dicarboxylic acid component of the copolymer polyester include one or more of isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, adipic acid, sebacic acid, etc., and examples of the glycol component include one or more of ethylene glycol, diethylene glycol, propylene glycol, 1,4-butanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, etc. Among these, the polyester film is preferably a polyethylene terephthalate having 60 mol % or more, preferably 80 mol % or more of ethylene terephthalate units, or a polyethylene-2,6-naphthalate having 60 mol % or more, preferably 80 mol % or more of ethylene-2,6-naphthalate units.

[0013] (intrinsic viscosity) The intrinsic viscosity of the polyester resin (X) is preferably 0.80 dL / g or less. When the intrinsic viscosity is 0.80 dL / g or less, the stability of melt extrusion is ensured. From the above viewpoints, the intrinsic viscosity of the polyester resin (X) is more preferably 0.70 dL / g or less. On the other hand, the lower limit of the intrinsic viscosity is not particularly limited, but is preferably 0.45 dL / g or more. When the intrinsic viscosity is 0.45 dL / g or more, the productivity during film production is maintained and sufficient mechanical strength of the film is ensured. From the above viewpoints, the intrinsic viscosity is more preferably 0.50 dL / g or more, and even more preferably 0.52 dL / g or more.

[0014] (Polyester polycondensation catalyst) Examples of the polycondensation catalyst used in obtaining the polyester by polycondensation include antimony compounds, germanium compounds, aluminum compounds, titanium compounds, etc. Among these, at least one of antimony compounds and titanium compounds is preferred, and it is particularly preferred to use a polyester obtained by using a titanium compound, i.e., to use a Ti-based polycondensation catalyst. Therefore, the polyester film preferably contains at least one of an antimony compound and a titanium compound, and more preferably contains a titanium compound (Ti-based). By using the titanium compound, it is possible to reduce the number of metal-containing aggregates, so-called coarse foreign matter, in the film that originates from the titanium compound.

[0015] (particle) Particles can be blended into the polyester resin (X) mainly for the purpose of imparting easy slippage and preventing scratches in each process. When particles are blended, the type of particles to be blended is not particularly limited as long as they are particles capable of imparting easy slippage, and specific examples include inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, and organic particles such as acrylic resin, styrene resin, urea resin, phenolic resin, epoxy resin, and benzoguanamine resin. Furthermore, precipitated particles obtained by precipitating and finely dispersing a part of a metal compound such as a catalyst during the polyester production process can also be used.

[0016] On the other hand, the shape of the particles to be used is not particularly limited, and any of spherical, blocky, rod-like, flat, etc. may be used. In addition, there is no particular limit to the hardness, specific gravity, color, etc. Two or more kinds of these particles may be used in combination as necessary. The average particle size of the particles used is preferably 3 μm or less, more preferably 0.1 to 2 μm, and particularly preferably in the range of 0.1 to 1 μm. By using particles having an average particle size in the above range, a suitable surface roughness can be imparted to the polyester film described later in detail, and good slipping properties and smoothness can be ensured. In addition, when particles are blended with the resin composition to form a polyester film, for example, a surface layer and an intermediate layer may be provided, and the particles may be contained in the surface layer. In this case, a multi-layer structure may be formed having a particle-containing surface layer, an intermediate layer, and a particle-containing surface layer in this order.

[0017] In addition, an embodiment in which the polyester resin (X) does not substantially contain particles is also preferred. Here, "substantially does not contain particles" means that the particles are not intentionally contained, and specifically means that the particle content (particle concentration) is 200 mass ppm or less, more preferably 150 mass ppm or less.

[0018] Since the resin composition of the present invention contains the polypropylene resin (Y) which is incompatible with the polyester resin (X) constituting the polyester, the polyester film formed from the resin composition of the present invention can form fine irregularities on the film surface due to the polypropylene resin (Y). Therefore, the amount of particles in the film can be made equal to or less than the upper limit, and the film can be easily imparted with slipperiness while ensuring the transparency of the film. In addition, when the polyester film does not contain particles or contains only a small amount of particles, the polyester film of the present invention described below has high transparency and has a good appearance, but the slipperiness may be insufficient. In such a case, it is advisable to improve the slipperiness by, for example, adding particles to the cured resin layer described below.

[0019] <Polypropylene resin (Y)> The polypropylene resin (Y) may be a homopolymer of propylene or a copolymer of propylene with ethylene and / or an α-olefin having 4 to 20 carbon atoms. In the present invention, the copolymerization component may be one type, or two or more types may be used in combination, if necessary.

[0020] The method for producing the polypropylene resin (Y) is not particularly limited, and may be a conventionally known method such as a method of polymerizing propylene and an arbitrary comonomer with a Ziegler-Natta catalyst, which is also described in Section 2.3.1 (pages 20-57) of "Polypropylene Handbook," edited by Edward P. Moore Jr., translated and supervised by Tetsuo Yasuda and Nobuo Sakuma, Kogyo Chosakai (1998).

[0021] (MFR (Melt Flow Rate)) The MFR of the polypropylene resin (Y) in the present invention is 7.0 g / 10 min or less. When the MFR is 7.0 g / 10 min or less, good fluidity can be ensured during film molding processing. From the above viewpoints, the MFR is preferably 5.0 g / 10 min or less, and more preferably 3.0 g / 10 min or less. The lower limit of the MFR is not particularly limited, but is, for example, 0.1 g / 10 min or more, preferably 0.2 g / 10 min or more, and more preferably 0.3 g / 10 min or more. The MFR was measured in accordance with ISO 1133-1:2011.

[0022] (Melting Point) The melting point of the polypropylene resin (Y) is preferably 150°C or higher, more preferably 160°C or higher. When the melting point is equal to or higher than the lower limit, the desired heat resistance can be ensured. The upper limit of the melting point is not particularly limited, but is usually 170°C. The melting point in the present invention can be determined by differential scanning calorimetry (DSC). Specifically, the temperature is once increased from room temperature to 200°C to erase the thermal history, and then the temperature is decreased to 40°C at a rate of 10°C / min, and the temperature is again measured at a rate of 10°C / min. The melting point is defined as the temperature of the endothermic peak top.

[0023] <Compatibilizer (Z)> The resin composition of the present invention contains a compatibilizer (Z). It is an essential requirement that the compatibilizer (Z) is a resin having an acid anhydride structure or an ionomer.

[0024] (Resin having an acid anhydride structure [-C(=O)-OC(=O)-]) The resin having an acid anhydride structure [-C(=O)-OC(=O)-] may be any resin having an acid anhydride structure [-C(=O)-OC(=O)-], and various resins may be used. Specifically, a polyolefin resin having the acid anhydride structure, such as polyethylene or polypropylene, or a polystyrene resin having an acid anhydride structure may be used. In particular, modified polypropylene resins having an acid anhydride structure (polypropylene resins modified with carboxylic acid anhydride) are preferred. The modified polypropylene resins having an acid anhydride structure are resins synthesized using a monomer having an acid anhydride structure in addition to propylene as a raw material. Modified polyethylene resins having an acid anhydride structure can also be used together with or instead of the modified polypropylene resins having an acid anhydride structure.

[0025] The monomer having an acid anhydride structure is preferably a compound having an acid anhydride structure and an ethylenically unsaturated bond.Specific examples include maleic anhydride, citraconic anhydride, aconitic anhydride, itaconic anhydride, etc., and among them, maleic anhydride is preferred in terms of improving the compatibility between the polyester resin (X) and the polypropylene resin (Y).

[0026] If the acid value of the resin having an acid anhydride structure [-C(=O)-OC(=O)-] is too small, the adhesive strength between the polyester resin (X) and the polypropylene resin (Y) may not be fully exhibited. On the other hand, if the acid value is too large, the compatibility with the resin decreases. Therefore, the acid value is preferably 0.5 to 50, more preferably 0.5 to 10. In addition, the MFR is preferably 2 to 20 g / 10 min, more preferably 3 to 10 g / 10 min. The acid value is a value measured in accordance with JIS K 0070.

[0027] Commercially available products can also be used as resins having an acid anhydride structure. For example, when a modified polypropylene resin is used, Admer (trade name, manufactured by Mitsui Chemicals), OREVAC (trade name, manufactured by Arkema), etc. can be used. When a modified polyethylene resin is used, Admer (trade name, manufactured by Mitsui Chemicals) LF128 (MFR; 2.7 g / 10 min), etc. can be used. In addition, when a styrene-based thermoplastic resin modified with maleic anhydride is used, examples thereof include "Tufprene 912" manufactured by Asahi Kasei Corporation, "FG1901" and "FG1924" manufactured by Kraton Polymer Japan, Ltd., and "Tuftec M1911", "Tuftec M1913", and "Tuftec M1943" manufactured by Asahi Kasei Corporation.

[0028] (Ionomer) An ionomer is a polymer chain formed by converting random, block, or graft copolymers of ethylene and an acidic vinyl monomer such as an unsaturated carboxylic acid into a partially neutralized metal salt, and then utilizing the cohesive force of the metal ions to form an aggregate. For example, there is an ionomer resin formed by neutralizing at least a portion of the carboxyl groups of an ethylene-unsaturated carboxylic acid copolymer resin with metal ions.

[0029] An ethylene-unsaturated carboxylic acid copolymer resin in which 10 mol % or more, preferably 10 to 90 mol %, and more preferably 15 to 80 mol % of the carboxyl groups are neutralized with a metal ion is preferably used. Examples of the metal ion include polyvalent metal ions such as alkali metals such as lithium and sodium, zinc, and alkaline earth metals such as magnesium and calcium. Among these, polyvalent metal ions such as zinc are preferred because of their good compatibilizing effect.

[0030] (Amount of polypropylene resin (Y)) The amount of polypropylene resin (Y) blended per 100 parts by mass of polyester resin (X) is preferably 1 to 30 parts by mass, more preferably 5 to 30 parts by mass, even more preferably 10 to 30 parts by mass, and particularly preferably 10 to 25 parts by mass. By satisfying the above range, the polyester film can have good electrical properties when used, for example, as a polyester film for a capacitor. In addition, when the polyester film formed from the resin composition is a multi-layer film, the above-mentioned blending amount is the blending amount in the entire polyester film. Therefore, for example, even in the case of a multi-layer polyester film formed using a resin composition having a different blending amount of polypropylene resin, it refers to the blending amount of polypropylene resin in the entire laminate film.

[0031] (Amount of compatibilizer (Z)) The amount of the compatibilizer (Z) to be blended relative to 100 parts by mass of the polyester resin (X) is preferably 0.01 to 40 parts by mass, more preferably 0.1 to 20 parts by mass, and particularly preferably 1 to 20 parts by mass. By satisfying the above range, the compatibility between the polyester resin (X) and the polypropylene resin (Y) becomes good, and it is possible to obtain a polyester film having good electrical properties as a polyester film for a capacitor. In addition, when the polyester film formed from the resin composition is a multi-layer film, the above-mentioned blending amount is the blending amount in the entire polyester film. Therefore, for example, even in the case of a multi-layer polyester film formed using resin compositions with different blending amounts of the compatibilizer, it refers to the blending amount of the compatibilizer in the entire laminate film. However, when only some of the layers have the polypropylene resin (Y) and only some of the layers have a layered structure, it is preferable that the some of the layers contain the compatibilizer (Z). The amount of the compatibilizer (Z) in the layer may be as described above, and the total amount does not necessarily have to be within the above range.

[0032] [Polyester film] The polyester film of the present invention (hereinafter sometimes referred to as "the polyester film") is made of the above-mentioned resin composition and has a thickness of 0.5 to 12.0 μm.

[0033] More specifically, the polyester film has a film thickness of 0.5 to 12.0 μm and contains a polyester resin (X), a polypropylene resin (Y) and a compatibilizer (Z), wherein the compatibilizer (Z) is a resin having an acid anhydride structure [-C(=O)-OC(=O)-] or an ionomer. The polyester resin (X), the polypropylene resin (Y) and the compatibilizer (Z) are as described above.

[0034] The polyester film will be described in more detail below. The polyester film has excellent physical properties such as heat resistance, flatness, optical properties, strength, etc. The polyester film may be a single layer or a multilayer film having two or more layers with different properties (that is, a laminated film). The polyester film may be a non-stretched film (sheet) or a stretched film. Of these, a stretched film stretched in a uniaxial or biaxial direction is preferable. Of these, a biaxially stretched film is more preferable from the viewpoint of balance of mechanical properties and flatness. Therefore, a biaxially stretched polyester film is even more preferable.

[0035] When the present film is a laminated film, it is preferable that the polyester constituting its outermost layer (also called the "surface layer", for example, the surface layer onto which the cured resin layer described below is laminated) uses a titanium compound as a polycondensation catalyst, and for example, it is preferable that the surface layer described below contains a titanium compound. The content of titanium element derived from the titanium compound in the outermost layer is preferably 3 ppm by mass or more and 40 ppm by mass or less, and more preferably 4 ppm by mass or more and 35 ppm by mass or less. Within the above range, the amount of foreign matter caused by the catalyst can be reduced without decreasing the production efficiency of the polyester. From the same viewpoint, the content of antimony compounds in the outermost layer of the present film is preferably 100 ppm by mass or less.

[0036] [Manufacturing method of polyester film] As an example of the method for producing the polyester film of the present invention (hereinafter referred to as the present production method), a production method in which the present polyester film is a biaxially stretched film will be described. However, the production method is not limited to the one described here.

[0037] First, using a known method, raw materials, such as polyester chips, are fed into a melt extrusion device, heated to above the melting point of each polymer, and the molten polymer is extruded through a die and cooled and solidified on a rotating cooling drum to a temperature below the glass transition point of the polymer, thereby obtaining an unoriented sheet in a substantially amorphous state. In this case, it is advisable to improve the dispersion by twin-screw kneading extrusion. By satisfying the following range, the polypropylene resin is finely dispersed in the polyester resin, and a film having good electrical properties can be obtained.

[0038] The extruder used in the present invention is preferably a vented twin-screw extruder having a raw material supply port and a vent opening in the cylinder, and at least one decompressed vent portion. The diameter (cylinder inner diameter) D (mm) of the twin-screw extruder used in the present invention is not particularly limited. The length L (mm) of the twin-screw extruder used in the present invention is preferably 20D (D is the cylinder inner diameter of the twin-screw extruder) to 50D, more preferably 25D to 45D. When L is 50D or less, the residence time in the extruder is not long, and the heat deterioration of the polyester and the incompatible polymer is not suppressed, which is preferable. On the other hand, when L is 20D or more, the polyester tends to be sufficiently plasticized, and as a result, stable melt extrusion is possible.

[0039] The draft ratio (lip gap / thickness of unstretched sheet) is preferably 40 or less, more preferably 35 or less, and even more preferably 25 or less. By satisfying the above range, the combination with the resin composition and the production conditions can be optimized, making it possible to produce a film with less unevenness in thickness and with less draw resonance.

[0040] The film thickness unevenness in the machine direction (MD) of the amorphous film is preferably 50 μm or less, more preferably 40 μm or less, and even more preferably 20 μm or less. By satisfying the above range, the draw resonance phenomenon is further prevented from occurring, and a biaxially stretched film can be obtained. The thickness unevenness was evaluated based on the difference between the thickness of the thickest part and the thickness of the thinnest part of the film, as described in the Examples.

[0041] Next, the unoriented sheet is stretched in one direction by a roll or tenter type stretching machine, at a stretching temperature of usually 25 to 120° C., preferably 35 to 100° C., and a stretching ratio of usually 2.5 to 7 times, preferably 2.8 to 6 times. Next, the film is stretched in a direction (TD, transverse) perpendicular to the first-stage stretching direction (MD, machine direction). The stretching temperature is usually 50 to 140° C., and the stretching ratio is usually 3.0 to 7 times, preferably 3.5 to 6 times. In this specification, stretching in the machine direction may be referred to as machine stretching, and stretching in the transverse direction may be referred to as transverse stretching. In the above stretching, a method in which the stretching in one direction is carried out in two or more stages can also be adopted. In the present invention, as described above, it is preferable to increase the stretch ratio in the transverse direction (TD direction), and it is preferable to set the stretch ratio to 4.5 times or more in either the first or second stage.

[0042] After the stretching, the film is subsequently heat-set at a temperature of 130 to 270° C. under tension or under relaxation of 30% or less, to obtain the present polyester film as a biaxially oriented film. The heat resistance of the polyester film can be improved by subjecting it to a heat setting treatment. When manufacturing a laminated polyester film having a multilayer structure as the present polyester film, the resin compositions constituting each layer are prepared and co-extruded to obtain a multilayer film. When co-extruding, all layers may be extruded under the above conditions, but at least one layer may be produced under the above extrusion conditions. For example, in the case of a three-layer structure of surface layer / middle layer / surface layer, only the middle layer may be extruded under the above conditions, or all layers may be extruded under the above conditions. The subsequent stretching and the like may be carried out in the same manner as above.

[0043] (film thickness) The thickness of the polyester film of the present invention is preferably 0.5 to 12.0 μm. When the thickness is in this range, the film is suitable for use, for example, as a capacitor. From the above viewpoints, the thickness of the polyester film of the present invention is more preferably 0.5 to 10.0 μm, and particularly preferably 1.0 to 8.0 μm.

[0044] <Characteristics of this polyester film> (Dielectric breakdown strength) The dielectric breakdown strength is preferably 250 kV / μm or more, more preferably 280 kV / μm or more, and particularly preferably 300 kV / μm or more. By satisfying the above range, good insulating properties can be obtained in a high-temperature atmosphere.

[0045] Specific means for forming the above structure include, for example, taking sufficient mixing time at the time of mixing the raw materials, setting the stretching ratio, particularly the transverse stretching ratio, to 4.0 times or more in terms of stretching conditions, selecting a type of polypropylene resin having an MFR of 0.1 to 10 g / 10 min or less, and using a compatibilizer in combination. These techniques may be used alone or in combination.

[0046] In the present invention, in order to accommodate capacitor applications, the film thickness is different from normal, and is predominantly in the ultra-thin range (0.5 to 12 μm). Therefore, it is different from other applications (for example, to provide cushioning as a paper replacement) in which voids are intentionally formed by using incompatible polypropylene resin with polyester resin. The reason for using polypropylene resin is, for example, that it is used as a film for a capacitor, particularly for the purpose of improving the withstand voltage characteristics. From this viewpoint, in order to improve periodic thickness unevenness (draw resonance) during film formation, as described above, the resin composition constituting the film is made to have a specific composition, more preferably, by setting the draft ratio in a predetermined range in the production conditions, it has been found that a film can be obtained that does not generate periodic thickness unevenness, has good continuous film formation properties, and has good electrical properties (e.g., dielectric breakdown strength) at high temperatures, for example, 150°C, and has been completed.

[0047] <Metal laminated film> The polyester film of the present invention can be made into a metal laminated film by providing a metal layer on at least one surface thereof. The metal laminated film is useful for a capacitor. Examples of metals include copper, silver, chromium, aluminum, nickel, zinc, etc., and among these, aluminum and zinc are preferred from the viewpoints of cost and environmental friendliness. The thickness of the metal layer is preferably in the range of 10 to 5000 Å, more preferably in the range of 100 to 4000 Å, and even more preferably in the range of 100 to 2000 Å. Being within the above range is advantageous in terms of electrical properties.

[0048] <Cured resin layer> The polyester film of the present invention may have a cured resin layer provided on its surface. The cured resin layer preferably contains a fluorine-containing compound. By providing a cured resin layer containing a fluorine-containing compound, the electrostatic potential per thickness is improved and the attenuation of the electrostatic potential can be further suppressed compared to the polyester film alone. In addition, dust and oil adhering to the polyester film surface can be easily removed. In particular, the cured resin layer is preferably formed by curing a cured resin layer composition containing a fluorine-containing compound (A), a crosslinking agent (B), and a binder resin (C). By using a cured resin layer composition containing these components (A) to (C), the cured resin layer can improve the electrostatic potential per thickness and further suppress attenuation of the electrostatic potential, and the cured resin layer is prevented from being scratched and has good solvent resistance, and the film-forming property and transparency of the cured resin layer are improved.

[0049] (Fluorine-containing compound (A)) The fluorine-containing compound is preferably a fluorine-containing resin from the viewpoint of increasing the strength of the cured resin layer.Specific examples of the fluorine-containing resin include fluoroolefin copolymer resins having vinyl fluoride, vinylidene fluoride, tetrafluoroethylene, hexafluoropropylene, chlorotrifluoroethylene, etc. as monomers; fluoromethylene ether, difluoromethylene ether, fluoroethylene ether, difluoroethylene ether, tetrafluoroethylene ether, hexafluoropropylene ether, etc., fluorine-containing copolymer resins obtained by polymerizing polyalkylene ethers in which some or all of the hydrogen atoms are substituted with fluorine atoms and other monomers; fluorine-containing copolymer resins obtained by graft polymerization of a hydroxyl group-containing fluororesin copolymer and a (meth)acrylic acid ester compound or other monomer; vinyl polymers having perfluoroalkyl groups, etc. are preferred.Among them, fluoroolefin copolymer resins and fluororesin copolymers containing polyalkylene ether groups in which some or all of the hydrogen atoms are fluorinated are preferred from the viewpoint of excellent improvement of the charged potential and excellent wiping properties of dust and oil.

[0050] Among the monomers of the fluoroolefin copolymer resin, vinylidene fluoride, tetrafluoroethylene, and hexafluoropropylene are preferred. Among the polyalkylene ethers in which some or all of the hydrogen atoms are replaced by fluorine atoms, difluoromethylene ether, difluoroethylene ether, and tetrafluoroethylene ether are preferred. When the fluorine-containing resin is made of a fluorine-containing monomer, it is preferred to use a mixed dispersion with other components from the viewpoint of dispersibility in a solvent and compatibility with other resins. The other components will be described later.

[0051] Examples of fluorine-based copolymer resins obtained by polymerizing a polyalkylene ether in which some or all of the hydrogen atoms have been substituted with fluorine atoms with other monomers include urethane resins having a polyfluoroalkylene ether group, polyester resins having a polyfluoroalkylene ether group, and acrylic resins having a polyfluoroalkylene ether group. Other monomers constituting the urethane resin having a polyfluoroalkylene ether group include isocyanate compounds. Examples of isocyanate compounds include aromatic diisocyanates such as tolylene diisocyanate, xylylene diisocyanate, methylene diphenyl diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, and tolidine diisocyanate; aliphatic diisocyanates having an aromatic ring such as α,α,α',α'-tetramethyl xylylene diisocyanate; aliphatic diisocyanates such as methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate; and alicyclic diisocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and isopropylidenedicyclohexyl diisocyanate.

[0052] Other monomers constituting the urethane resin include polyols not containing fluorine atoms, and polyols having a carboxy group such as dimethylolpropanoic acid, dimethylolbutanoic acid, bis-(2-hydroxyethyl)propionic acid, bis-(2-hydroxyethyl)butanoic acid, etc. Among these, it is preferable to include a polyol having a carboxy group from the viewpoint of self-emulsification when water is used as the dispersion solvent, and among these, dimethylolpropanoic acid is more preferable.

[0053] The cured resin layer is preferably formed from a cured resin layer-forming composition containing a fluorine-containing compound. The cured resin layer-forming composition (hereinafter referred to as "cured resin layer composition") may be composed of a fluorine-containing compound as a non-volatile component, or may contain other components. The content of the fluorine-containing compound in the cured resin layer composition is preferably 5 to 100% by mass, more preferably 20 to 98% by mass, and even more preferably 45 to 95% by mass, based on the non-volatile components in the cured resin layer composition. By making it 5% by mass or more, it is possible to improve the electrostatic potential per thickness and further suppress the attenuation of the electrostatic potential. In addition, it is possible to easily remove dust and oil adhering to the polyester film surface.

[0054] (Crosslinking agent (B)) As described above, the cured resin layer composition for forming the cured resin layer preferably contains a crosslinking agent (B). By including a crosslinking agent in the cured resin layer composition, a dense cured resin layer with high crosslink density can be formed. In addition, scratches on the cured resin layer can be prevented, and solvent resistance can be easily improved. The crosslinking agent is not particularly limited, and a conventionally known crosslinking agent can be used. Examples of the crosslinking agent include melamine compounds, oxazoline compounds, epoxy compounds, isocyanate compounds, carbodiimide compounds, and silane coupling compounds. The crosslinking agent is preferably at least one selected from melamine compounds, oxazoline compounds, and isocyanate compounds, and is preferably a melamine compound from the viewpoint of curability. These crosslinking agents may be used alone or in combination of two or more. In addition, any polymerizable monomer may be contained in the cured resin layer composition as a component that cures together with these crosslinking agents.

[0055] (Melamine compounds) The melamine compound used as the crosslinking agent is a compound having a melamine skeleton in the compound, and for example, an alkylolated melamine derivative, a compound obtained by reacting an alkylolated melamine derivative with an alcohol to partially or completely etherify it, and a mixture thereof can be used. Examples of alkylolation include methylolation, ethylolation, isopropylolation, n-butyrolation, isobutyrolation, etc. Among these, methylolation is preferred from the viewpoint of reactivity. As the alcohol used for etherification, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-butanol, isobutanol, etc. are preferably used. From the viewpoint of improving the coating strength of the cured resin layer and improving the adhesion between the cured resin layer and the polyester film, a partially or completely etherified alkylol melamine derivative is preferable, and an alkylol etherified with methyl alcohol is more preferable. The partially etherified alkylol group is preferably 0.5 to 5 equivalents, more preferably 0.7 to 5 equivalents, relative to the non-etherified alkylol group. The melamine compound may be a monomer or a dimer or higher polymer, or a mixture of these. Furthermore, a melamine compound obtained by co-condensing urea or the like with a part of the melamine may be used.

[0056] In order to increase the reactivity of the melamine compound, the cured resin layer composition may contain a crosslinking catalyst in addition to the melamine compound.As the crosslinking catalyst, various known catalysts can be used, for example, amine compounds, salts of amine compounds, organic acids such as aromatic sulfonic acid compounds such as paratoluenesulfonic acid and phosphoric acid compounds and their salts, imine compounds, amidine compounds, guanidine compounds, organometallic compounds, metal salts such as zinc stearate, zinc myristate, aluminum stearate, and calcium stearate, etc.Among these, amine compounds, salts of amine compounds, and paratoluenesulfonic acid are preferred, and amine compounds and salts of amine compounds are more preferred.

[0057] (Oxazoline compounds) The oxazoline compound is a compound having an oxazoline group in the molecule, and a polymer containing an oxazoline group is particularly preferred, and the polymer can be prepared by polymerization of an addition polymerizable oxazoline group-containing monomer alone or with other monomers. Among them, an acrylic polymer that is a copolymer of an addition polymerizable oxazoline group-containing monomer and an acrylic monomer that is a monomer having a (meth)acryloyl group is preferred, and the acrylic polymer may have a polyalkylene oxide chain. In this specification, when the expression "(meth)acryloyl group" is used, it means one or both of "acryloyl group" and "methacryloyl group", and the same applies to other similar terms. Examples of the addition polymerizable oxazoline group-containing monomer include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline, and one or more of these can be used in combination. Among these, 2-isopropenyl-2-oxazoline is industrially easily available and is suitable. The addition polymerizable oxazoline group-containing monomer may be used alone, or two or more monomers can be used.

[0058] The other monomer is not limited as long as it is a monomer that can be copolymerized with the addition-polymerizable oxazoline group-containing monomer, and examples thereof include (meth)acrylic acid esters such as alkyl (meth)acrylates (alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, 2-ethylhexyl, and cyclohexyl groups); unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, and styrenesulfonic acid and their salts (salts include sodium salts, potassium salts, ammonium salts, and tertiary amine salts); unsaturated nitriles such as acrylonitrile and methacrylonitrile; (meth)acrylic acid, Examples of the alkyl group include unsaturated amides such as acrylamide, N-alkyl(meth)acrylamide, and N,N-dialkyl(meth)acrylamide (alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, 2-ethylhexyl, and cyclohexyl groups); vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether and ethyl vinyl ether; α-olefins such as ethylene and propylene; halogen-containing α,β-unsaturated monomers such as vinyl chloride, vinylidene chloride, and vinyl fluoride; and α,β-unsaturated aromatic monomers such as styrene and α-methylstyrene.

[0059] As the other monomer, a monomer having a polyalkylene oxide chain can also be used. Preferred examples of the monomer having a polyalkylene oxide chain include esters in which a polyalkylene oxide is added to a carboxy group of an unsaturated carboxylic acid such as acrylic acid or methacrylic acid. Preferred examples of the polyalkylene oxide chain include polymethylene oxide, polyethylene oxide, polypropylene oxide, and polybutylene oxide. The number of repeating units of the polyalkylene oxide chain may be, for example, in the range of 3 to 100. The other monomers used in the oxazoline compound may be used alone or in combination of two or more kinds.

[0060] The amount of oxazoline groups in the oxazoline compound is preferably in the range of 0.5 to 10 mmol / g, more preferably 1 to 9 mmol / g, further preferably 3 to 8 mmol / g, and particularly preferably 4 to 6 mmol / g. By using it in the above range, the durability of the coating film (cured resin layer) is likely to be improved.

[0061] (Epoxy compounds) The epoxy compound is a compound having an epoxy group in the molecule, and examples thereof include condensates of epichlorohydrin with hydroxyl- or amino-group-containing compounds such as ethylene glycol, polyethylene glycol, glycerin, polyglycerin, and bisphenol A. Examples of the epoxy compound include polyepoxy compounds, diepoxy compounds, monoepoxy compounds, and glycidylamine compounds. Examples of polyepoxy compounds include sorbitol polyglycidyl ether, polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, triglycidyl tris(2-hydroxyethyl)isocyanate, glycerol polyglycidyl ether, and trimethylolpropane polyglycidyl ether. Examples of diepoxy compounds include neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, resorcinol diglycidyl ether, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and polytetramethylene glycol diglycidyl ether. Examples of the monoepoxy compound include allyl glycidyl ether, 2-ethylhexyl glycidyl ether, and phenyl glycidyl ether. Examples of the glycidylamine compound include N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylamino)cyclohexane, etc. The epoxy compounds may be used alone or in combination of two or more.

[0062] (Isocyanate compounds) The isocyanate-based compound is a compound having an isocyanate or an isocyanate derivative structure, such as a blocked isocyanate. Examples of the isocyanate include aromatic isocyanates such as tolylene diisocyanate, xylylene diisocyanate, methylene diphenyl diisocyanate, phenylene diisocyanate, and naphthalene diisocyanate; aliphatic isocyanates having an aromatic ring such as α,α,α',α'-tetramethyl xylylene diisocyanate; aliphatic isocyanates such as methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate; and alicyclic isocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, methylene bis(4-cyclohexyl isocyanate), and isopropylidenedicyclohexyl diisocyanate. In addition, polymers and derivatives such as biuretized products, isocyanurate products, and uretdione products of these isocyanates are also included. These isocyanates may be used alone or in combination. Among the above isocyanates, aliphatic isocyanates or alicyclic isocyanates are more preferred in order to prevent yellowing due to ultraviolet rays.

[0063] When used in the form of a blocked isocyanate, examples of the blocking agent include bisulfites such as sodium bisulfite, phenolic compounds such as phenol, cresol, and ethylphenol; alcohol compounds such as propylene glycol monomethyl ether, ethylene glycol, benzyl alcohol, methanol, and ethanol; active methylene compounds such as dimethyl malonate, diethyl malonate, methyl acetoacetate, ethyl acetoacetate, and acetylacetone; mercaptan compounds such as butyl mercaptan and dodecyl mercaptan; lactam compounds such as ε-caprolactam and δ-valerolactam; amine compounds such as diphenylaniline, aniline, and ethyleneimine; acid amide compounds such as acetanilide and acetic acid amide; and oxime compounds such as formaldehyde, acetaldoxime, acetoneoxime, methyl ethyl ketoneoxime, and cyclohexanoneoxime. These may be used alone or in combination of two or more.

[0064] The isocyanate compound may be used alone or in combination with various polymers. The isocyanate compound may be blended in the cured resin layer composition as a mixture of various polymers. From the viewpoint of improving the dispersibility and crosslinking property of the isocyanate compound, it is preferable to use a mixture or combination with a polyester resin or a urethane resin. The isocyanate compound may be used alone or in combination of two or more. The amount of the crosslinking agent when the isocyanate compound is used includes the amount of the blocking agent, the polymer to be blended by binding or mixing, and the like.

[0065] (Carbodiimide compounds) A carbodiimide compound is a compound having a carbodiimide structure. The use of a carbodiimide compound can improve the wet heat resistance of the cured resin layer. A carbodiimide compound can be synthesized by a conventionally known technique, and generally, a condensation reaction of a diisocyanate compound is used. The diisocyanate compound is not particularly limited, and both aromatic and aliphatic compounds can be used, and specific examples thereof include tolylene diisocyanate, xylene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexyl diisocyanate, and dicyclohexylmethane diisocyanate. The carbodiimide compound may be used alone or in combination of two or more.

[0066] (Silane coupling compound) A silane coupling compound is an organosilicon compound that has an organic functional group and a hydrolyzable group such as an alkoxy group in one molecule. For example, epoxy group-containing compounds such as 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; vinyl group-containing compounds such as vinyltrimethoxysilane and vinyltriethoxysilane; styryl group-containing compounds such as p-styryltrimethoxysilane and p-styryltriethoxysilane; (meth)acrylic group-containing compounds such as 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, and 3-(meth)acryloxypropylmethyldiethoxysilane; 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)- Amino group-containing compounds such as 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, and N-phenyl-3-aminopropyltriethoxysilane; isocyanurate group-containing compounds such as tris(trimethoxysilylpropyl)isocyanurate and tris(triethoxysilylpropyl)isocyanurate; mercapto group-containing compounds such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, and 3-mercaptopropylmethyldiethoxysilane. Among the above compounds, from the viewpoint of maintaining the strength of the cured resin layer, epoxy group-containing silane coupling agents, double bond-containing silane coupling agents such as vinyl groups or (meth)acrylic groups, and amino group-containing silane coupling agents are more preferred. The silane coupling agent may be used alone or in combination of two or more kinds.

[0067] The crosslinking agent contained in the cured resin layer composition may be designed to react during the drying process or film-forming process when forming the cured resin layer to improve the performance of the cured resin layer. It can be assumed that the cured resin layer formed from the cured resin layer composition contains unreacted crosslinking agents, reacted compounds, or mixtures thereof.

[0068] The content of the crosslinking agent in the cured resin layer composition is preferably in the range of 5 to 60% by mass relative to the non-volatile components in the cured resin layer composition. By setting the content of the crosslinking agent to 5 to 60% by mass relative to the non-volatile components in the cured resin layer composition, it becomes easier to suppress the attenuation of the electrostatic potential. In addition, the strength of the cured resin layer is improved, and scratch resistance and the like are also easily improved. From the above viewpoints, it is more preferably 10 to 50% by mass, further preferably 15 to 40% by mass, and particularly preferably 20 to 40% by mass.

[0069] In addition, when a crosslinking catalyst is contained in the cured resin layer composition, the content of the crosslinking catalyst is preferably in the range of 0.4 to 10 mass% based on the non-volatile components in the cured resin layer composition. When the content of the crosslinking catalyst is in the range of 0.4 to 10 mass%, the strength of the cured resin layer tends to be improved and scratch resistance tends to be improved, which is preferable. From the above viewpoints, the content of the crosslinking catalyst is preferably 0.6 to 8 mass%, more preferably 0.8 to 5 mass%.

[0070] (Binder resin (C)) The binder resin is a polymer component contained in the cured resin layer composition other than the polymer crosslinked by the crosslinking agent (B). When the cured resin layer composition contains the binder resin, the film-forming property, transparency, etc. of the cured resin layer are improved.

[0071] Specific examples of binder resins include acrylic resins, polyvinyl alcohol, polyester resins, urethane resins, polyalkylene glycols, polyalkyleneimines, methyl cellulose, hydroxycellulose, starches, etc. Among these, from the viewpoint of coatability, etc., acrylic resins, polyester resins, and urethane resins are preferred, from the viewpoint of improving the durability of the cured resin layer itself, acrylic resins and polyester resins are more preferred, and from the viewpoint of further improving coatability, etc., acrylic resins are even more preferred.

[0072] (Acrylic resin) The acrylic resin is a polymer made of polymerizable monomers including acrylic and methacrylic monomers. These may be homopolymers or copolymers, or copolymers with polymerizable monomers other than acrylic and methacrylic monomers. Also included are copolymers of these polymers with other polymers (such as polyesters and polyurethanes). For example, block copolymers and graft copolymers. That is, the acrylic resin may be an acrylic-modified polyester resin or an acrylic-modified polyurethane resin. Further, it also includes a polymer (or a mixture of polymers in some cases) obtained by polymerizing a polymerizable monomer in a polyester solution or polyester dispersion. Similarly, it also includes a polymer (or a mixture of polymers in some cases) obtained by polymerizing a polymerizable monomer in a polyurethane solution or polyurethane dispersion. Similarly, it also includes a polymer (or a mixture of polymers in some cases) obtained by polymerizing a polymerizable monomer in another polymer solution or dispersion, and these are also referred to as acrylic modified polyester resins and acrylic modified polyurethane resins in this specification. The above-mentioned polyesters and polyurethanes used in the acrylic resins can be appropriately selected from those exemplified as polyesters and polyurethanes used in the binder resins described later. The acrylic resin may contain a hydroxyl group or an amino group in order to further improve adhesion to the polyester film.

[0073] The polymerizable monomer is not particularly limited, but particularly representative compounds include various carboxyl group-containing monomers such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid, fumaric acid, maleic acid, and citraconic acid, and salts thereof; various hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, monobutyl hydroxyl fumarate, and monobutyl hydroxy itaconate; methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, lauryl (meth)acrylate, and the like. various nitrogen-containing compounds such as (meth)acrylamide, diacetone acrylamide, N-methylolacrylamide, or (meth)acrylonitrile; various styrene derivatives such as styrene, α-methylstyrene, divinylbenzene, or vinyltoluene; various vinyl esters such as vinyl propionate; various silicon-containing polymerizable monomers such as γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, or the like; phosphorus-containing vinyl monomers; various vinyl halides such as vinyl chloride and vinylidene chloride; and various conjugated dienes such as butadiene.

[0074] (polyester resin) The polyester resin may be composed of, for example, the following polyvalent carboxylic acid and polyvalent hydroxy compound as main components. That is, as the polyvalent carboxylic acid, terephthalic acid, isophthalic acid, orthophthalic acid, phthalic acid, 4,4'-diphenyldicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2-potassium sulfoterephthalic acid, 5-sodium sulfoisophthalic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, glutaric acid, succinic acid, trimellitic acid, trimesic acid, pyromellitic acid, trimellitic anhydride, phthalic anhydride, p-hydroxybenzoic acid, trimellitic acid monopotassium salt, and ester-forming derivatives thereof may be used. Examples of polyhydric hydroxy compounds include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 2-methyl-1,5-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, p-xylylene glycol, bisphenol A-ethylene glycol adduct, diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polytetramethylene oxide glycol, dimethylolpropionic acid, glycerin, trimethylolpropane, sodium dimethylolethylsulfonate, and potassium dimethylolpropionate. One or more of these compounds may be appropriately selected and a polyester resin may be synthesized by a conventional polycondensation reaction. The polyester resin may be made into an aqueous dispersion, and in this case, a hydrophilic functional group or the like may be appropriately introduced into the polyester resin.

[0075] (Polyvinyl alcohol) Polyvinyl alcohol is a compound having a polyvinyl alcohol moiety. For example, conventionally known polyvinyl alcohols can be used, including modified compounds in which polyvinyl alcohol is partially acetalized or butyralized. The degree of polymerization of polyvinyl alcohol is not particularly limited, but is usually 100 or more, preferably in the range of 300 to 40,000. By setting the degree of polymerization to 100 or more, it is possible to prevent the water resistance of the cured resin layer from decreasing. In addition, the degree of saponification of polyvinyl alcohol is not particularly limited, but a polyvinyl acetate saponification product having a degree of saponification of usually 70 mol % or more, preferably in the range of 70 to 99.9 mol %, more preferably 80 to 97 mol %, and particularly preferably 86 to 95 mol % is practically used.

[0076] (urethane resin) The urethane resin is a polymeric compound having a urethane bond in the molecule. Usually, the urethane resin is produced by the reaction of a polyol with an isocyanate. The polyol may be polycarbonate polyols, polyester polyols, polyether polyols, polyolefin polyols, or acrylic polyols, and these compounds may be used alone or in combination. The urethane resin may be a water dispersion, and in this case, for example, a hydrophilic functional group may be appropriately introduced into the polyol.

[0077] The content of the binder resin in the cured resin layer composition is preferably in the range of 10 to 70% by mass relative to the non-volatile components in the cured resin layer composition. By setting the content of the binder resin to 10 to 70% by mass, it becomes easier to suppress the attenuation of the coating property and the electrostatic potential. In addition, it becomes easier to improve the appearance and transparency of the cured resin layer. From the above viewpoints, it is more preferably 20 to 65% by mass, further preferably 30 to 60% by mass, and particularly preferably 30 to 55% by mass. In addition to the above-mentioned components, the cured resin layer composition may contain additives such as a reaction regulator, an adhesion enhancer, a surfactant, an antistatic agent, and particles.

[0078] The cured resin layer composition may be applied to a polyester film as a liquid coating solution, and then dried and cured as necessary. The cured resin layer composition is preferably diluted with a solvent to prepare a coating solution. The above-mentioned components (such as components (A) to (C)) constituting the cured resin composition may be dissolved in a solvent, or may be dispersed in the solvent. There is no limitation on the solvent used in the cured resin layer composition, and either water or an organic solvent may be used, but from the viewpoint of environmental protection, it is preferable to use an aqueous coating liquid in which water is used as a solvent. The aqueous coating liquid may contain a small amount of organic solvent. The specific amount of organic solvent should be less than water on a mass basis, and is, for example, less than 30 mass% in the solvent, preferably less than 20 mass%, more preferably less than 10 mass%. Examples of organic solvents used in combination with water include alcohols such as ethanol, isopropanol, ethylene glycol, and glycerin; ethers such as ethyl cellosolve, t-butyl cellosolve, propylene glycol monomethyl ether, and tetrahydrofuran; ketones such as acetone and methyl ethyl ketone; esters such as ethyl acetate; and amines such as dimethylethanolamine. These can be used alone or in combination. By appropriately selecting and adding these organic solvents to the aqueous coating liquid as necessary, the stability and coatability of the coating liquid may be improved.

[0079] In addition, when an organic solvent is used alone as the above-mentioned solvent, examples of the organic solvent include aromatic hydrocarbons such as toluene, aliphatic hydrocarbons such as hexane, heptane, isooctane, esters such as ethyl acetate, butyl acetate, ketones such as ethyl methyl ketone (MEK), isobutyl methyl ketone, alcohols such as ethanol, 2-propanol, ethers such as diisopropyl ether, dibutyl ether, etc. These may be used alone or in combination, taking into consideration solubility, coatability, boiling point, etc.

[0080] <Method of forming cured resin layer> The method for forming the cured resin layer will be described in detail below. The cured resin layer may be formed by in-line coating or off-line coating. In-line coating is a method of applying a coating liquid of a cured resin layer composition to the surface of a polyester film on a production line for producing the polyester film. Off-line coating is a method of applying a coating liquid outside the system (outside the above-mentioned production line) onto a polyester film that has already been produced. It is preferable to form the cured resin layer by in-line coating from the viewpoint of ease of processing.

[0081] Specifically, in-line coating is a method of applying a coating liquid of a cured resin layer composition to a polyester film at any stage from melt extrusion of polyester to stretching, heat setting and winding up. Usually, the coating liquid is applied to the polyester film in any of the following stages: an unstretched sheet obtained by melting and quenching, a stretched uniaxially stretched film, a biaxially stretched film before heat setting, and a film after heat setting and before winding up.

[0082] Examples of the method for applying the coating liquid include air doctor coating, blade coating, rod coating, bar coating, knife coating, squeeze coating, impregnation coating, reverse roll coating, transfer roll coating, gravure coating, kiss roll coating, cast coating, spray coating, curtain coating, calendar coating, and extrusion coating.

[0083] Also, although not particularly limited, for example, in the case of sequential biaxial stretching, a method is preferred in which a coating liquid is applied to a uniaxially stretched film that has been particularly stretched in the longitudinal direction (machine direction) and then stretched in the transverse direction. According to such a method, since the polyester film and the cured resin layer can be formed simultaneously, there is an advantage in terms of production cost, and since stretching is performed after coating, the thickness of the cured resin layer can be changed by the stretching ratio, and thin film coating can be performed more easily than offline coating. Furthermore, the thickness of the cured resin layer can be made more uniform.

[0084] Furthermore, by applying a coating liquid of the cured resin layer composition onto the polyester film before stretching, the cured resin can be stretched together with the polyester film, thereby allowing the cured resin layer to adhere firmly to the polyester film. In addition, in the production of a biaxially stretched film, the polyester film can be restrained in the longitudinal and lateral directions by stretching while holding the film ends with clips or the like, and in the heat setting step, it can be heated to a high temperature while maintaining its flatness without wrinkles, etc. Therefore, the heat treatment performed after application of the cured resin layer composition can be performed at a high temperature that cannot be achieved by other methods, and the cured resin layer and the polyester film can be more firmly adhered to each other.

[0085] In addition, the coating solution of the cured resin layer composition applied to the polyester film may be subjected to either heat treatment or irradiation with active energy rays such as ultraviolet rays, or both may be used in combination, but it is preferable to at least perform heat treatment. In addition, the cured resin layer composition may be cured by one or both of heat treatment and irradiation with active energy rays. The heat treatment may be performed by heating in a heat setting process as described above, but may also be performed by other methods. In addition, when the coating solution of the cured resin layer composition contains a solvent, it is appropriately dried, but it is preferable to dry it by the above-mentioned heat treatment. In order to improve the coatability of a coating liquid for forming a cured resin layer onto the polyester film and the adhesion of the cured resin layer to the polyester film, the surface of the polyester film on which the cured resin layer is to be formed may be subjected to a surface treatment such as a chemical treatment, a corona discharge treatment, a plasma treatment, an ozone treatment, a chemical treatment, a solvent treatment or the like before the coating liquid is applied.

[0086] As described above, the polyester film with the cured resin layer may have another layer between the polyester film and the cured resin layer. Examples of the other layer include layers having various functions such as an antistatic layer, an easy-adhesion layer, and an oligomer sealing layer.

[0087] The thickness of the cured resin layer is preferably 0.005 to 1 μm. By making the thickness 1 μm or less, the components constituting the cured resin layer are prevented from migrating to the cured resin layer, etc., and furthermore, blocking during winding is easily prevented. On the other hand, by making the thickness 0.005 μm or more, the attenuation of the electrostatic potential is more easily suppressed. From these viewpoints, the thickness of the cured resin layer is more preferably 0.01 μm or more, further preferably 0.02 μm or more, and is more preferably 0.2 μm or less, further preferably 0.1 μm or less, and particularly preferably 0.06 μm or less.

[0088] <Explanation of terms, etc.> In the present invention, the term "film" includes the term "sheet", and the term "sheet" includes the term "film". In the present invention, when it is described as "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as the meaning of "preferably larger than X" or "preferably smaller than Y". In addition, when it is stated that the amount is "X or more" (X is any number), it also means that the amount is "preferably greater than X" unless otherwise specified, and when it is stated that the amount is "Y or less" (Y is any number), it also means that the amount is "preferably smaller than Y" unless otherwise specified. EXAMPLES

[0089] The present invention will now be described in more detail with reference to examples, although the present invention is not limited to the examples described below.

[0090] <Evaluation method> The methods for measuring and evaluating various physical properties and characteristics are as follows.

[0091] (1) Intrinsic viscosity (IV) 1 g of polyester was precisely weighed, dissolved in 100 ml of a mixed solvent of phenol / tetrachloroethane = 50 / 50 (weight ratio), and measured at 30°C.

[0092] (2) Melting point of polypropylene resin (Y) In differential scanning calorimetry (DSC), the sample is heated from room temperature to 200°C, the thermal history is erased, the temperature is then lowered to 40°C at a rate of 10°C / min, and the sample is again heated at a rate of 10°C / min. This is defined as the temperature at the top of the endothermic peak.

[0093] (3) Uneven film thickness Measurements were made using a continuous film thickness measuring device manufactured by Anritsu (using an electronic micrometer, measuring length: 4 m). Thickness unevenness was evaluated based on the difference (R) in thickness between the thickest and thinnest parts of the film.

[0094] (4) Draw Resonance (DR) Phenomenon For each amorphous sheet obtained in the Examples and Comparative Examples, the thickness unevenness in the running direction (MD) was measured using a continuous film thickness measuring device manufactured by Anritsu Corporation (using an electronic micrometer, measuring length: 4 m). The thickness unevenness was evaluated based on the difference (R) between the thickness of the thickest part and the thickness of the thinnest part of the film. Judgment criteria ◎: R value is 20 μm or less. ○: R value is greater than 20 μm and less than 40 μm. △: R value is over 40 μm and 50 μm or less. ×: R value exceeds 50 μm.

[0095] (5) Continuous film formation When the amorphous sheets of the Examples and Comparative Examples were biaxially stretched to obtain polyester film rolls, the case where the rolls could be obtained without breakage was judged as good (◯), and the case where breakage occurred frequently and it was difficult to obtain the rolls was judged as poor (×). 〇: Roll collection possible (good continuous film production) ×: Difficult to obtain rolls (frequent breakages, poor continuous film production)

[0096] (6) Dielectric breakdown strength Measurements were taken using a Yamayo Test Instruments Co., Ltd. AC 50kV / DC 10kV insulation breakdown tester YST-243AT-B model, and in air, using equal diameter electrodes (25mm cylinder x 25mm cylinder), applying an AC voltage at a ramp rate of 100V / sec.

[0097] The raw materials of the polyester films in the respective Examples and Comparative Examples are as follows. (Polyester film) (a) Polyester resin (X1): Polyethylene terephthalate homopolymer having an intrinsic viscosity of 0.63 (polycondensation catalyst: titanium). (b) Polyester resin (X2): polyethylene terephthalate homopolymer having an intrinsic viscosity of 0.55 (polycondensation catalyst: antimony). (c) Polyester resin (X3): polyethylene terephthalate homopolymer (polycondensation catalyst: titanium) containing 0.5% by mass of resin particles having an average particle size of 0.3 μm and having an intrinsic viscosity of 0.61. (d) Polyester resin (X4): Polyethylene terephthalate homopolymer (polycondensation catalyst: antimony) containing 0.6 mass % of silica particles having an average particle size of 2.3 μm and having an intrinsic viscosity of 0.61. (e) Polypropylene resin (Y1): melting point 163°C, MFR = 7.5 (Sumitomo Chemical Co., Ltd.: FLX80E4) (f) Polypropylene resin (Y2): melting point 165°C, MFR = 20 (Japan Polypropylene Corporation: MA1B) (g) Polypropylene resin (Y3): melting point 167°C, MFR = 15 (Prime Polymer: J106G) (h) Polypropylene resin (Y4): melting point 166°C, MFR = 0.5 (Japan Polypropylene Corporation: EA9) (i) Resin having an acid anhydride structure (Z1): Maleic anhydride modified polypropylene resin (Admer QE800, melt flow rate: 9.1 g / 10 min, acid value: 4.3, manufactured by Mitsui Chemicals, Inc.)

[0098] [Example 1] 73.5% by mass of polyester X1, 14% by mass of polyester X4, 10% by mass of polypropylene Y4, and 2.5% by mass of compatibilizer Z1 were mixed, and melt-extruded into a film at 285°C using a vented twin-screw extruder (cylinder aperture D = 47 mm, screw rotation direction = same direction rotation), and then quenched and solidified using an electrostatic adhesion method on a rotating cooling drum at 25°C to obtain an amorphous film. The total extrusion rate (Q) at this time was 14 (kg / hour), the screw rotation speed (N) was 70 (rpm), and the line speed was 10 m / min. The evaluation results are shown in Table 1.

[0099] [Examples 2 to 6] An amorphous film was obtained in the same manner as in Example 1, except that the components in Example 1 were changed to those shown in Table 1. The evaluation results are shown in Table 1.

[0100] [Example 7] The amorphous film obtained in Example 3 was simultaneously stretched 3.5 times in both the longitudinal and transverse directions at a stretching temperature of 100° C. using an Imoto Manufacturing Co., Ltd. film biaxial stretching device IMC-11A9. The obtained film was sandwiched and fixed between SUS frames and heat-set for 15 seconds in an oven at 220° C. to obtain a polyester film with a thickness of 6.8 μm. The evaluation results are shown in Table 2.

[0101] [Comparative Examples 1 to 3] An amorphous film was obtained in the same manner as in Example 1 except that the conditions were changed as shown in Table 1.

[0102] [Comparative Example 4] The amorphous film obtained in Comparative Example 1 was simultaneously stretched 3.5 times in both the longitudinal and transverse directions at a stretching temperature of 100°C using an Imoto Manufacturing Co., Ltd. film biaxial stretching device IMC-11A9. The obtained film was clamped and fixed between SUS frames and heat-set for 15 seconds in an oven at 220°C to obtain a polyester film with a thickness of 6.8 μm. The evaluation results are shown in Table 2.

[0103] [Table 1]

[0104] [Table 2]

[0105] It was found that in Examples 1 to 6, since the MFR of the polypropylene resin (Y) was 7.0 or less, the draw resonance phenomenon was unlikely to occur. In addition, it was found that if the thickness unevenness of the amorphous film is 50 μm or less, the film can be continuously produced without any problems in the subsequent stretching process. Furthermore, a comparison between Example 3 and Example 6 showed that the film thickness unevenness improvement effect was further increased by reducing the draft ratio. Furthermore, it is clear from Table 2 that the use of the resin composition of the present invention makes it possible to obtain electrical properties (dielectric breakdown strength) comparable to those of conventional resins. On the other hand, in all of Comparative Examples 1 to 3, the MFR of the polypropylene resin (Y) exceeded 7.0, and the occurrence of the draw resonance phenomenon was visually confirmed. The film thickness unevenness was also poor, and breakage occurred frequently in the stretching process, indicating poor continuous film formability. [Industrial Applicability]

[0106] The resin composition of the present invention and the polyester film obtained by using the resin composition are polyester films that have good heat resistance, can be made thin, and have small thickness unevenness while maintaining electrical properties comparable to those of conventional polyester films, and are therefore extremely useful for capacitors and have high industrial value.

Claims

1. A resin composition comprising a polyester resin (X), a polypropylene resin (Y) and a compatibilizer (Z), and satisfying the following (1) and (2): (1) The polypropylene resin (Y) has an MFR (melt flow rate) of 7.0 g / 10 min or less. (2) The compatibilizer (Z) is a resin or ionomer having an acid anhydride structure [--C(=O)--O--C(=O)--].

2. The resin composition according to claim 1, comprising 0.01 to 40 parts by mass of a compatibilizer (Z) relative to 100 parts by mass of the polyester resin (X).

3. The resin composition according to claim 1, comprising 1 to 30 parts by mass of polypropylene resin (Y) per 100 parts by mass of polyester resin (X).

4. The resin composition according to claim 1, wherein the polyester resin (X) has an intrinsic viscosity of 0.80 dL / g or less.

5. The resin composition according to claim 1, wherein the polyester resin (X) is at least one selected from polyethylene terephthalate and polyethylene-2,6-naphthalate.

6. The resin composition according to claim 1, wherein the polycondensation catalyst for the polyester resin (X) is a Ti-based catalyst.

7. A polyester film comprising the resin composition according to any one of claims 1 to 6.

8. The polyester film according to claim 7, having a thickness of 0.5 to 12.0 μm.

9. The polyester film has a thickness of 0.5 to 12.0 μm and comprises a polyester resin (X), a polypropylene resin (Y) and a compatibilizer (Z), wherein the compatibilizer (Z) is a resin having an acid anhydride structure [—C(═O)—O—C(═O)—] or an ionomer.

10. 8. The polyester film according to claim 7, which has a dielectric breakdown strength of 250 kV / μm or more.

11. The method for producing a polyester film according to claim 7, wherein the amorphous film has a thickness variation of 50 μm or less in the running direction.

12. The method for producing a polyester film according to claim 11, wherein the draft ratio (lip gap / thickness of unstretched sheet) is 40 or less.

13. A metal laminated film comprising the polyester film according to claim 7 and a metal layer provided on at least one surface of the polyester film.

Citation Information

Patent Citations

  • Biaxially oriented polypropylene film for capacitor

    JP2014231584A